CHEMISTRY OF NEUTRAL AND ALKALINE WATERS WITH LOW AL3+ ACTIVITY AGAINST HYDROXYALUMINOSILICATE HASB SOLUBILITY. THE EVIDENCE FROM GROUND AND SURFACE WATERS OF THE SUDETES MTS. (SW POLAND) - Dobrzyński D. (My University, 2007)
A wide set of aqueous chemistry data (574 water analyses) from natural environments has been used to testify and validate of the solubility of synthetic hydroxyaluminosilicate (HASB), Al2Si2O5(OH)4. The ground and surface waters represent regolith and/or fissure aquifers in various (magmatic, sedimentary and metamorphic) bedrocks in the Sudetes Mts. (SW Poland). The solubility of HASB in natural waters was calculated using the method proposed by Schneider et al. (Polyhedron 23:3185–3191, 2004). Results confirm usefulness and validity of this method. The HASB solubility obtained from the field data (logKsp=−44.7±0.58) is lower than it was estimated (logKsp=−40.6±0.15) experimentally (Schneider et al. Polyhedron 23:3185–3191, 2004). In the waters studied the equilibrium with HASB is maintained at pH above 6.7 and at [Al3+]≤10−10. Silicon activity (log[H4SiO4]) ranges between −4.2 and −3.4. Due to the calculation method used, the Ksp mentioned above cannot be considered as a classical solubility constant. However, it can be used in the interpretation of aluminium solubility in natural waters. The HASB has solubility lower than amorphous Al(OH)3, and higher than proto-imogolite. From water samples that are in equilibrium with respect to HASB, the solubility product described by the reaction, \textAl\text2 \textSi\text2 \textO\text5 \text(OH)\text4 \text + \text6H\text + « \text2Al\text3+ \text + \text2H\text4 \textSiO\text4 \text + \textH\text2 \textO {\text{Al}}_{{\text{2}}} {\text{Si}}_{{\text{2}}} {\text{O}}_{{\text{5}}} {\text{(OH)}}_{{\text{4}}} \;{\text{ + }}\;{\text{6H}}^{{\text{ + }}} \; \leftrightarrow \;{\text{2Al}}^{{{\text{3+}}}} \;{\text{ + }}\;{\text{2H}}_{{\text{4}}} {\text{SiO}}_{{\text{4}}} \;{\text{ + }}\;{\text{H}}_{{\text{2}}} {\text{O}} is calculated to be logKsp=14.0 (±0.7) at 7°C.
Keywords: HYDROXYALUMINOSILICATE; NATURAL WATER; POLAND; SUDETES MTS; WATER CHEMISTRY